Butterfly Hug Therapy in Leaving Self-Acceptance to Generation Z - Ayunda Ramadhani; Lisda Sofia; Raudatun Nisa; Herlina Amelia Putri (Universitas Aisyah Pringsewu, 2023)
This study aims to increase self-acceptance in the z generation using butterfly hug. This research uses quantitative methods. The subjects in this study were 15 students of the Psychology Study Program at Univeristas Mulawarman who were selected using a purposive sampling. The data collection method used was self-acceptance scale. The collected data were analyzed with the help of the SPSS 26.0 for windows. The results of this study show that 1) There is a significant increase in self-acceptance in the experimental group with p=0.046. Then H1 is accepted and H0 is rejected, which means there is a significant self-improvement after being given the butterfly hug. 2) There is a significant increase in self-acceptance in the experimental control group with a value of p=0.000. So, there are differences in self-acceptance scores before and after in the control group which was not given the butterfly hug. 3) There is a difference in the level of self-acceptance with a value of p = 0.042 between the experimental group (given treatment) and the control group (no treatment).Abstrak: Penelitian ini bertujuan untuk meningkatkan penerimaan diri pada generasi z menggunakan terapi butterfly hug. Penelitian ini menggunakan metode kuantitatif. Subjek dalam penelitian ini adalah 15 mahasiswa Program Studi Psikologi di Universitas Mulawarman yang dipilih dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan adalah dengan skala penerimaan diri. Data yang terkumpul dianalisis dengan bantuan program SPSS 26.0 for windows. Hasil penelitian ini menunjukkan bahwa 1) Terdapat peningkatan terhadap penerimaan diri yang signifikan di kelompok eksperimen dengan nilai p=0.046. Maka H1 diterima dan H0 ditolak yang artinya terdapat peningkatan diri yang signifikan setelah diberikan perlakuan terapi butterfly hug. 2) Terdapat peningkatan terhadap penerimaan diri yang signifikan di kelompok kontrol eksperimen dengan nilai p=0.000. Maka ada perbedaan skor penerimaan diri sebelum dan sesudah pada kelompok kontrol yang tidak diberikan perlakuan terapi butterfly hug. 3) Terdapat perbedaan tingkat penerimaan diri dengan nilai p=0.042 antara kelompok eksperimen (diberikan perlakuan) dan kelompok kontrol (tidak diberikan perlakuan).